1989
DOI: 10.1177/0022022189203005
|View full text |Cite
|
Sign up to set email alerts
|

Individualism-Collectivism and Pyschological Needs

Abstract: Two studies were conducted to examine the relationship between the dimension of individualism versus collectivism and psychological needs. In the first study Chinese subjects in Hong Kong completed an Individualism-Collectivism Scale and the Edwards Personal Preference Schedule. Collectivism was found to be positively related to the needs for affiliation, succorance, abasement, and nurturance and negatively related to the needs for autonomy, deference, and heterosexuality. In the second study, American subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(111 citation statements)
references
References 13 publications
1
103
0
5
Order By: Relevance
“…Individual behavior relating to group processes and personality (16) As some of these studies are only tangentially related to organizational contexts and are more social psychological in focus (e.g., Hui and Villareal, 1989;Oyserman, 1993;Yamaguchi et al, 1995;Kwan et al, 1997;Wojciszke, 1997;Oyserman et al, 1998;Grimm et al, 1999;Tafarodi et al, 1999;Carpenter and Radhakrishnan, 2000;Satterwhite et al, 2000), we highlight only those that have clear links to work-related outcomes. For example, Triandis et al (1988) conducted three studies to examine the relationship between IND and COL and self-ingroup relations.…”
Section: Reward Allocation (8)mentioning
confidence: 99%
“…Individual behavior relating to group processes and personality (16) As some of these studies are only tangentially related to organizational contexts and are more social psychological in focus (e.g., Hui and Villareal, 1989;Oyserman, 1993;Yamaguchi et al, 1995;Kwan et al, 1997;Wojciszke, 1997;Oyserman et al, 1998;Grimm et al, 1999;Tafarodi et al, 1999;Carpenter and Radhakrishnan, 2000;Satterwhite et al, 2000), we highlight only those that have clear links to work-related outcomes. For example, Triandis et al (1988) conducted three studies to examine the relationship between IND and COL and self-ingroup relations.…”
Section: Reward Allocation (8)mentioning
confidence: 99%
“…Individualistic cultures, which include most Western countries (Mau, 2004) usually, promote independence and individual autonomy (Hui & Villareal, 1989;Mau, 2004 found that Asian-Americans had greater difficulties then Caucasian-Americans, in both highschool and college samples. Another study by Mau (2001) found that Taiwanese undergraduate students experienced more career decision-making difficulties than American students.…”
Section: Cultural Differences In Career Decision-makingmentioning
confidence: 99%
“…Individualistic cultures, which include most Western countries (Mau, 2004) usually, promote independence and individual autonomy (Hui & Villareal, 1989;Mau, 2004). Whereas collectivistic cultures, which include most Asian, Latin…”
Section: Cultural Differences In Career Decision-makingmentioning
confidence: 99%
“…In most societies, women tend to be more collectivistic than men, while upperclass, urban, and younger samples tend to be more individualistic (Triandis, 1995). While traditional Chinese culture has long been regarded by some social scientists as collectivist, individualist elements do exist (Hui & Villareal, 1989).…”
Section: Individualism and Collectivismmentioning
confidence: 99%